Pertunjukan Tari Musikal GENTA LOKA: EKSPLORASI TRUNTUNG DAN SENG DALAM PERTUNJUKAN TARI MUSIKAL : GENTA LOKA: EKSPLORASI TRUNTUNG DAN SENG DALAM PERTUNJUKAN TARI MUSIKAL - Eko Pebo, Eko Supendi; Sri Kuncoro, Jonet; suroto (GETER : Jurnal Seni Drama, Tari dan Musik, 2025)
ABSTRACT Genta Loka is an artistic research project that develops trunthung musicality through the integration of percussive sounds generated from recycled zinc sheets. Using a practice-based research framework, the study positions creative processes—sound exploration, instrument construction, choreographic development—as epistemic modes. The work investigates acoustic characteristics of metal waste, timbral expansion of trunthung, and the formation of hybrid bodily movement through interactions among Soreng dance, hip-hop, and contemporary dance vocabularies. Results indicate that metal waste introduces new timbral layers, enriches rhythmic structures, and shapes distinctive dramaturgy. The project also emphasizes cultural ecology by highlighting recycled materials as artistic and ecological agents.